2018
DOI: 10.5267/j.ijiec.2017.4.004
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and analysis of tool wear and surface roughness in hard turning of AISI D2 steel using response surface methodology

Abstract: The present work deals with some machinability studies on tool wear and surface roughness, in finish hard turning of AISI D2 steel using PCBN, Mixed ceramic and coated carbide inserts. The machining experiments are conducted based on the response surface methodology (RSM). Combined effects of three cutting parameters viz., cutting speed, cutting time and tool hardness on the two performance outputs (i.e. VB and Ra), are explored employing the analysis of variance (ANOVA).The relationship(s) between input varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The results show that workpiece hardness has a significant effect on flank wear. Junaid et al (2018) analyzed a series of machinability studies focusing on tool wear and surface roughness in the finishing hard turning of AISI D2 steel utilizing PCBN, mixed ceramic, and coated carbide inserts. The findings indicate that tool wear was primarily influenced by cutting time and, to a lesser extent, by the hardness of the cutting tool.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that workpiece hardness has a significant effect on flank wear. Junaid et al (2018) analyzed a series of machinability studies focusing on tool wear and surface roughness in the finishing hard turning of AISI D2 steel utilizing PCBN, mixed ceramic, and coated carbide inserts. The findings indicate that tool wear was primarily influenced by cutting time and, to a lesser extent, by the hardness of the cutting tool.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can be applied for specific cases in which only several factors were considered in the investigation of their influence on the tool wear and surface roughness [7][8][9]. Therefore, many studies focused on experimental modeling methods with a limited amount of input parameters [15][16][17][18][19]. In the experimental modelling method, many approaches were applied to model the tool wear and surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The response surface method was applied to analyze the effect of the technological parameters on the tool wear and surface roughness. Besides, using this method, the tool wear and surface roughness were also modeled [15][16][17][18][19]. Taguchi method was used to design the experimental matrix, to investigate the influence of technological parameters and cutting conditions on the tool wear and surface roughness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the results it was revealed that the cutting time altered the tool wear. On the other hand, cutting time was the principal factor influencing the surface roughness of the workpiece succeeded by cutting speed [10]. Deshpande and Pant has conducted the experiments on EN8 alloy steel material with the PVD coated TiAlN insert and plain carbide insert by Taguchi method.…”
Section: Introductionmentioning
confidence: 99%